A facile approach to the fabrication of rattle-type magnetic carbon nanospheres for removal of methylene blue in water. (August 2015) - Shao, Yanming; Zhou, Lincheng; Bao, Chao; Ma, Junjun
Abstract: Rattle-type magnetic carbon nanospheres were obtained easily by annealing core–shell–shell hybrid nanospheres. The nanospheres were fabricated by combining, in a single step, a tetraethyl orthosilicate sol–gel process and the condensation polymerization of resorcinol and formaldehyde in the presence of ammonia. Subsequent annealing and silicon dioxide removal in sodium hydroxide solution resulted in materials with a high specific surface area (250.3 m 2  g −1 ) that could be separated easily from aqueous media using an external magnetic field. Methylene blue was selected as a typical organic pollutant to test adsorption and Fenton catalytic degradation performance. The results demonstrate the potential applicability of the rattle-type magnetic carbon nanospheres. The nanospheres could remove methylene blue rapidly with an adsorption capacity of 45.15 mg g −1 . They can also effectively catalyze the degradation of methylene blue because of their special structure.